Durable inequality - Tilly, Charles (University of California Press, 1998)
Charles Tilly, in this eloquent manifesto, presents a powerful new approach to the study of persistent social inequality. How, he asks, do long-lasting, systematic inequalities in life chances arise, and how do they come to distinguish members of different socially defined categories of persons? Exploring representative paired and unequal categories, such as male/female, black/white, and citizen/noncitizen, Tilly argues that the basic causes of these and similar inequalities greatly resemble one another.
Keywords: Income distribution.; Equality.; Revenu -- Répartition.; POLITICAL SCIENCE -- Economic Conditions.; BUSINESS & ECONOMICS -- Economics -- Macroeconomics.; SOCIAL SCIENCE -- Discrimination & Race Relations.; Equality; Income distribution; Soziale Ungleichheit; Personelle Einkommensverteilung; Lohngleichheit; Einkommensverteilung; Sociale ongelijkheid.; Inkomensverdeling.; adaptation.; analysis.; binary.; capitalism.; categorical pairs.; categories.; contemporary.; cultural history.; cultural studies.; dualism.; equality.; exploitation.; feminism.; feminist.; government.; inequality.; manifesto.; nationalism.; philosophy.; political.; politics.; representation.; social history.; social inequality.; social justice.; social studies.; systemic inequality.; systemic racism.; Electronic book.